UiTM and Cardiff University strengthen global partnership through MoU exchange - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
AAGBS management headed by the Dean of AAGBS accompanied the delegates from Cardiff University, Wales, United Kingdom to UiTM's Vice Chancellor's office. The Vice Chancellor YBhg. Profesor Datuk Dr. Shahrin bin Sahib @ Sahibuddin warmly welcomed the delegates from Cardiff led by Professor Rudolf Allemann, the Pro Vice-Chancellor, International and Student Recruitment and Head of the College of Physical Sciences and Engineering. After brief introductions, they discussed potential areas of partnership and expressed mutual interest in academic exchanges and research initiatives. The meeting concluded with an exchange of Memorandums of Understanding documents.